High-quality AlN epitaxy on sapphire substrates with sputtered buffer layers. (May 2017) - Zhang, Lisheng; Xu, Fujun; Wang, Mingxing; Sun, Yuanhao; Xie, Nan; Wang, Tao; Dong, Boyu; Qin, Zhixin; Wang, Xinqiang; Shen, Bo
Abstract: In this work, a novel strategy for high-quality AlN templates epitaxy on sapphire substrates with sputtered buffer layers combined with a low- and high-temperature alteration technique is proposed. The best full width at half maximum values for (0002) and (1 1 ¯ 02) reflections are 207 and 377 arcsec, respectively. Investigations indicate the joint effect of growth mode control and sputtered buffer layer results in the improvement of AlN crystalline quality. Firstly, threading dislocations density can be significantly decreased due to the alteration from three-dimensional to two-dimensional growth mode. Moreover, the graded composition of AlON layer in the sputtered buffer layer is believed to alleviate lattice mismatch between sapphire substrates and AlN, which also contributes to low dislocations density in AlN templates. Highlights: A novel strategy for high-quality AlN epitaxy on sapphire substrates with sputtered buffer layers combined with a low- and high-temperature alteration technique is proposed. Threading dislocations density was significantly decreased due to the alteration of growth mode. The graded composition of AlON layer is believed to alleviate lattice mismatch between sapphire and AlN.